Diamomix By Ec-Cook / Azhani Zulkapli - Zulkapli, Azhani; Hasri, Nurhasya Irdina; Sharil, Nur Shamira; Hashim, Nurul Haszirah; Halim, Nuruliyana Farisha (2022)
In this age of technology, everyone wants to take an easy way out to do something. Including cooking at home, some people are so busy with their jobs out there that they don’t have time to cook food at home. Because of that, they choose to buy food outside without knowing whether the food is clean or not. In addition, some people are not good at cooking, especially people who are single or newly married, with this tool they can cook because with this tool everything is available such as examples, how to cook, the weight of ingredients that need to be included for cooking and others. The purpose of this study was to find information on whether this tool can be marketed outside and whether it will be accepted by consumers. We will run a questionnaire to gather information and seek feedback from outsiders. In conclusion, with the existence of this product may be able to help those who do not have time or busy with work as well as help people who are not good at cooking.